Antara Lelucon dan Kritik: Kolom Komentar Akun X @memeunivrse sebagai Cermin Keresahan Sosial Netizen Pendekatan Pragmatik - Jamhur, Nuratika; Hasbi, Nur (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2025)
This study aims to examine the form of speech acts and implicit meaning in the comments of @memeunivrse account users that contain social criticism content. The approach used is qualitative with descriptive-analytical method. Data were obtained through observation and documentation of comments on several @memeunivrse account uploads. The analysis technique used refers to the theory of pragmatics, especially speech acts and implicatures developed by Austin and Searle. The results of the analysis show that netizen comments contain hidden meanings in the form of social criticism of various phenomena such as moral crisis, weak public services, and degradation of cultural values. Comments are delivered in the form of expressive, assertive, and subtle insinuations. This finding shows that social media has become an important medium for people to convey criticism indirectly through clever and meaningful linguistic strategies.